Alcohol consumption and breast cancer risk subtypes in the E3N-EPIC cohort. Issue 3 (May 2015) - Fagherazzi, Guy; Vilier, Alice; Boutron-Ruault, Marie-Christine; Mesrine, Sylvie; Clavel-Chapelon, Françoise
<x xml:space="preserve">Abstract</x> The aim of this study was to obtain an overview of the associations between alcohol consumption and breast cancer risk at adulthood, by type of alcohol and subtype of breast cancer. Between 1993 and 2008, 66 481 women from the French E3N-EPIC cohort were followed up and asked to report their alcohol consumption, by type of alcohol, through a 208-item diet-history questionnaire. A total of 2812 breast cancer cases were validated during the follow-up session. No association was found between high alcohol consumption, whatever its type, and increase in breast cancer risk in the premenopausal period. During the postmenopausal period, a linear association between total alcohol consumption and breast cancer risk was found (P<0.0001), mainly driven by the associations with wine and beer [hazard ratio=1.33 (1.11–1.58) and 1.85 (1.19–2.89)] for more than two glasses per day of wine and beer, respectively, compared with nondrinkers] and with ER+/PR+ breast cancer subtypes. In the postmenopausal period, we observed interactions between total alcohol and folate intake levels (P=0.1192) and BMI (P=0.0367), with higher increased risks observed for high alcohol intake among women with low folate intake or who were overweight or obese. Our results make precise the current body of knowledge on the relationship between alcohol and breast cancer subtypes. Interactions between alcohol and other factors should further be taken into account in public health nutrition programs.